Answer:
11, 7, 3, -1, -5
Explanation:
The dependent variable y is often used interchangeably with the function value f(x). That is, we can usually presume that ...
y = f(x)
__
evaluate the function
To find f(x), put the value of x everywhere x appears in the function definition, and do the arithmetic. A calculator or spreadsheet can relieve some of the boredom of repetition. Here are a couple of examples.
f(-2) = -4(-2) +3 = 8 +3 = 11
f(-1) = -4(-1) +3 = 4 +3 = 7
time saver
You may notice that each increase of 1 in the value of x causes a decrease of 4 in the value of y. That means we can simply subtract 4 from the previous value of y to find the next one:

__
Attached is an example of this table being filled by a calculator.